China Outbound Tourism: A Bibliometric Review from 2008-2024 - Natrudee, Intatip (Indonesian Journal of Advanced Research, 2025)
This paper examines a substantial yet distributed body of research on outbound tourism from China in the hospitality sector. To ascertain the general performance and research themes in this area, we used bibliometric and content analyses on 1,484 peer-reviewed English articles published between 2008 and 2024. Co-occurrence analysis was used to identify four key research themes: (1) Factors affecting Chinese tourists' decision to travel abroad, (2) Economic Determinants of inhouse and Cross-Border Investment, (3) Business and Stakeholder Strategy, and (4) Technology and Innovation-Driven Markets. Factors affecting Chinese tourists' decision to travel abroad mainly consist of three subthemes: determinants of Chinese satisfaction behaviors, experience in niche tourism and special events, and impacts from social media platforms. Subthemes pertaining to Economic Determinants of in-house and Cross-Border Investment involve politics and government direction. The subthemes of Business and Stakeholder Strategy determinants primarily focus on tourism stakeholder outcomes, stakeholder relationship quality, and China’s tourism destination trust. Subthemes within Technology and Innovation-Driven Markets include how they transform the tourism market in several significant ways. This work enhances our understanding of the progress, prediction of the future and limitations of research on China Outbound Tourism.